2023
DOI: 10.1101/2023.01.20.524909
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of caffeine and other xanthines on liver sinusoidal endothelial cell ultrastructure

Abstract: Xanthines such as caffeine and theobromine are among the most consumed psychoactive stimulants in the world, either as natural components of coffee, tea and chocolate, or as food additives. The present study assessed if xanthines affect liver sinusoidal endothelial cells (LSEC). Cultured primary rat LSEC were challenged with xanthines at concentrations typically obtained from normal consumption of xanthine-containing beverages, food or medicines; and at higher concentrations below the in vitro toxic limit. The… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Pathologists were formerly obligated to employ electron microscopy and other histochemical staining methods, such as hematoxylin and eosin, to identify potential changes brought on by specific pathogenic organisms [31]. A significant change was brought about by the broad availability and specificity of antibody reagents.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologists were formerly obligated to employ electron microscopy and other histochemical staining methods, such as hematoxylin and eosin, to identify potential changes brought on by specific pathogenic organisms [31]. A significant change was brought about by the broad availability and specificity of antibody reagents.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many scholars have studied methylxanthine in recent years and found that it also has antioxidant [6] , anti-in ammatory [7] , anti-cancer [8] , and lipolysis effects [9] . Further, it is known to inhibit SARS-CoV-2-related virus [10] and reverse the age-related decrease in porosity of liver sinusoidal endothelial cells [11] with many other bene cial effects. Currently, there are few reports on the correlation between theobromine intake and periodontitis, so we used the NHANES large database to explore the correlation between theobromine and periodontitis.…”
Section: Introductionmentioning
confidence: 99%